The forest’s subjectivity - Najder-Stefaniak, Krystyna (Studia Ecologiae et Bioethicae, 2019)
The author finds justification for ‘forest rights’ in the subjective existence of ecosystems. The concept of life helps her to understand the subjectivity of ecosystems. She notes that the specificity of life is the creative duration that connects the three dimensions of time: past, present and future. Thinking about dependencies in the ecosystemrelation scheme helps to understand how it is possible to be so creative. The author uses the concept of the ‘subject of responsibility’, which is found in Roman Ingarden’s work ‘On Responsibility and its Ontical Foundations’. Being the subject of responsibility justifies having rights that allow you to contribute to the pursuit of TRUTH, GOOD and BEAUTY. Thanks to ecosystem activity, which is the forest itself, these three universal values can be realized.